2009
DOI: 10.1111/j.1365-2583.2009.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization, expression pattern and cellular distribution of an ovarian lipophorin receptor in the cockroach, Leucophaea maderae

Abstract: A cDNA that encodes a lipophorin receptor (LpR) with a predicted structure similar to that of the low density lipoprotein receptor (LDLR) gene superfamily was cloned from ovaries of the cockroach, Leucophaea maderae (Lem) and characterized. This is the first LpR sequenced from the order Dictyoptera. The cDNA has a length of 3362 bp coding for an 888-residue mature protein with a predicted molecular mass of ~99.14 kDa and a p I value of 4.68. The deduced amino acid sequence showed that the LemLpR harbours eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…The VgRs of insects have large membrane bound proteins approximately 180–214 kDa in size [62]. The molecular characterization of insect VgRs has revealed that these receptors, regardless of their origin, are extremely conserved not only in their structure but also in terms of their regulation [21, 63]. VgR plays a crucial role in insect reproduction but little is known about this receptor in insects compared to its ligand, the Vg.…”
Section: Discussionmentioning
confidence: 99%
“…The VgRs of insects have large membrane bound proteins approximately 180–214 kDa in size [62]. The molecular characterization of insect VgRs has revealed that these receptors, regardless of their origin, are extremely conserved not only in their structure but also in terms of their regulation [21, 63]. VgR plays a crucial role in insect reproduction but little is known about this receptor in insects compared to its ligand, the Vg.…”
Section: Discussionmentioning
confidence: 99%
“…Most insect eggs contain large supplies of nutrients to support embryogenesis and oogenesis is commonly a nutrient-limited process [ 60 ]. The proteins accumulate in insects developing oocytes [ 61 ] and amounts of lipophorins are found in ovaries at different stages of the reproduction cycle in B. germanica [ 62 ] and Panstrongylus megistus [ 63 ]. Lipid is also another essential component for the journey to insect reproduction [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In insects, lipids are transported by the Lp from the fat body to oocytes through receptor mediated endocytosis [ 18 , 33 ]. Generally, the expression of LpR transcripts was observed throughout the ovarian development and increased during vitellogenesis of several insect species including A .…”
Section: Discussionmentioning
confidence: 99%